2021
DOI: 10.1089/heq.2020.0120
|View full text |Cite|
|
Sign up to set email alerts
|

Social Determinants of Health in Maternity Care: A Quality Improvement Project for Food Insecurity Screening and Health Care Provider Referral

Abstract: Purpose: This quality improvement project evaluated implementation of social determinants of health screening and referral for food insecurity. Methods: Four obstetric providers used study-developed resources to screen and refer English-speaking patients ( n =14) during clinic visits. Providers and patients completed post-visit questionnaires. Provider feedback informed improvements to the intervention approach for consecutive study shifts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…One previous study has reported high participant satisfaction with a healthcare‐based intervention to address food insecurity during pregnancy. In this small, quasi‐experimental study, Fitzhugh et al 74 offered an emergency food package to pregnant women who answered affirmatively to the Health Vital Sign, a validated two‐item food insecurity screening tool, as well as a third item that aimed to identify urgent need for food. Survey‐measured participant satisfaction was ‘positive’, with over 71% of participants rating their healthcare experience as ‘extremely’ satisfactory 74 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One previous study has reported high participant satisfaction with a healthcare‐based intervention to address food insecurity during pregnancy. In this small, quasi‐experimental study, Fitzhugh et al 74 offered an emergency food package to pregnant women who answered affirmatively to the Health Vital Sign, a validated two‐item food insecurity screening tool, as well as a third item that aimed to identify urgent need for food. Survey‐measured participant satisfaction was ‘positive’, with over 71% of participants rating their healthcare experience as ‘extremely’ satisfactory 74 .…”
Section: Discussionmentioning
confidence: 99%
“…In this small, quasi‐experimental study, Fitzhugh et al 74 offered an emergency food package to pregnant women who answered affirmatively to the Health Vital Sign, a validated two‐item food insecurity screening tool, as well as a third item that aimed to identify urgent need for food. Survey‐measured participant satisfaction was ‘positive’, with over 71% of participants rating their healthcare experience as ‘extremely’ satisfactory 74 . Further research into the efficacy and acceptability of healthcare‐based interventions is needed to ensure that the needs of food‐insecure pregnant women can be met within the resource limitations of antenatal clinics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,36 Similarly, there are limitations in the international literature. While these studies may have larger cohorts, there is a focus on a few specific determinants, such as food insecutity 37 and homelessness 38 or specific populations. 39 A systematic review of birth outcomes in high-income countries found common determinants of poor outcome, such as poverty, but confirmed studies were usually focussed on a few variables or general population indicators (e.g.…”
Section: Introductionmentioning
confidence: 99%